PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN DALAM PERKARA KORUPSI PADA PUTUSAN NOMOR 51/Pid.Sus-TPK/2024/PN Jkt Pst - Laurencia Dian Flaviana Agatha; Bambang Santoso (Sebelas Maret University, 2025)
This study aims to assess the appropriateness of using expert testimony as evidence in the proving corruption cases, specifically in verdict Number 51/Pid.Sus-TPK/2024/PN Jkt. Pst. This research is normative legal research and it is prescriptive in nature, with legal sources obtained from primary and secondary legal resources. The technique of collecting legal in this research is by means of literature study and legal materials are obtained and processed using the deductive syllogism method. The author analyzes Articles 2 and 3 of the Law on the Against of Corruption Crime as the major premise, with Verdict Number 51/Pid.SusTPK/2024/PN Jkt. Pst. as the minor premise.The results showed that the judge's considerations in imposing a criminal sentence are consistent with Article 183 of KUHAP. In their legal reasoning, the panel of judges based their decision on the evidence and exhibits presented, which convinced them, coupled with the absence of any findings of the criminal irresponsibility.